2019
DOI: 10.1080/13811118.2019.1624667
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and Acceptability of the Youth Aware of Mental Health (YAM) Intervention in US Adolescents

Abstract: Care. The funders of this research had no role in the study design, analysis, interpretation of results, or preparation of this paper. The content is the sole responsibility of the authors and does not necessarily represent the official views of any of the funders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 38 publications
2
16
0
Order By: Relevance
“…In the current study, consent/assent was 50.7%. This rate is higher than the pilot study of YAM in Montana (37%; Lindow et al, 2019) and similar to three other studies on school-based mental health promoting/suicide prevention requiring consent for youth (35%–69%; Schilling et al, 2014, 2016; Wyman et al, 2010), and higher than one not requiring consent (19% and 10%; Wyman et al, 2008). However, two other studies not requiring consent reported significantly higher participation (>90%; Aseltine & Demartino, 2004; Aseltine et al, 2007; Hart et al, 2018).…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…In the current study, consent/assent was 50.7%. This rate is higher than the pilot study of YAM in Montana (37%; Lindow et al, 2019) and similar to three other studies on school-based mental health promoting/suicide prevention requiring consent for youth (35%–69%; Schilling et al, 2014, 2016; Wyman et al, 2010), and higher than one not requiring consent (19% and 10%; Wyman et al, 2008). However, two other studies not requiring consent reported significantly higher participation (>90%; Aseltine & Demartino, 2004; Aseltine et al, 2007; Hart et al, 2018).…”
Section: Discussionsupporting
confidence: 75%
“…Results of this study indicate that the YAM intervention delivered by extension agents was feasible and acceptable for rural school settings as assessed by school and student recruitment, intervention fidelity, assessment completion rates, and extension agent feedback. Student surveys showed high satisfaction with YAM delivered by extension agents, which tended to be at least as positive as those from delivered by non-Extension facilitators (Lindow et al, 2019). This may be due to extension agents having experience working with youth especially using experiential methods such as role-play.…”
Section: Discussionmentioning
confidence: 98%
“…Results of empirical studies (Cwik et al, 2016; Katz et al, 2013; Robinson et al, 2018; Schilling et al, 2016; Singer et al, 2019) have indicated that universal suicide education can reduce suicidal behaviors among student populations. Among existing programs of this type that are designed for secondary students, Signs of Suicide (SOS; MindWise Innovations, 2020) and Youth Aware of Mental Health (YAM; Lindow, Hughes, South, Gutierrez, et al, 2020; Lindow, Hughes, South, Minhajuddin, et al, 2020), both of which combine other prevention strategies (school-wide screening) with suicide education, are the only two that have yielded statistically significant support for their effectiveness in reducing suicidal thoughts and behaviors among students (Katz et al, 2013; Lindow, Hughes, South, Gutierrez, et al, 2020; Robinson et al, 2013; Singer et al, 2019). Regarding programs fashioned for students at lower grade levels, only one, the Good Behavior Game (GBG; Education Development Center [EDC], 2013), has produced statistically significant evidence for its efficacy in curtailing suicidal ideation among young children (Singer et al, 2019; Wilcox et al, 2008).…”
Section: Review Of Literaturementioning
confidence: 99%
“…In the 2017-2018 and 2018-2019 academic years, a mental health promotion program was delivered to 1,000 of high school students in North Texas. This program was an expansion of a two-state study examining the feasibility and acceptability of the mental health promotion program (Lindow et al, 2020). As part of the mental health promotion program, a subset of students (n = 3,222) assented to participate in a research study to evaluate the program.…”
Section: Study Design and Participantsmentioning
confidence: 99%